IMPLEMENTASI PENDEKATAN SCIENTIFIC DALAM PENGAJARAN BAHASA INGGRIS KURIKULUM 2013 DI SMPN 1 PAMEKASAN - Azizah, Siti; Ariwidodo, Eko; Adriana, Iswah (OKARA: Jurnal Bahasa dan Sastra, 2015)
This article is a summary of a group research describing the implementation of scientific approach in teaching English of Curriculum 2013 at SMPN 1 Pamekasan. Scientific approach is an approach focusing on investigation techniques onÂ phenomena, getting new knowledge, or correcting and relating the previous knowledge. Scientific approach is a new approach in teaching English. This research has three study focuses that is: 1) How the English teachers Â of the seventh grade plan English learning process by using scientific approach 2) How the implemntation of scientific approach in teaching English of Curriculum 2013 at SMPN 1 Pamekasan 3) What problems or difficulties faced by the English teachers in implementing the scientific approach. The Research result showsÂ the first,Â English teachers of the seventh grade at SMPN 1 Pamekasan plan their English learning process by writing the lesson plan first. Second, the implementation of scientific approach in teaching English of Curriculum 2013 at SMPN 1 Pamekasan on the first year does not run well. Third, most of English teachers of the seventh grade at SMPN 1 Pamekasan get difficulties in facilitating the students to ask and answer theÂ Â questions to their friends or teacher. It means that the teachers still get difficulties in questioning step of scientific approach.